Pengruh Penerapan Metode Pembelajaran Kooperatif Berbasis Kasus yang Berpusat pada Mahasiswa Terhadap Efektivitas Pembelajaran Akuntansi Keperilakuan - Siti Mutmainah (The Indonesian Journal of Accounting Research, 2013)
Traditional learning model that puts dominant lecturer as a center of gravity in the classroom has embedded weaknesses.  In this traditional model, an instructor looks like if she or he is a source of knowledge.  On the other hand, students are no more than a "copying machine" where they listen and make a copy of the lecture for the day.   The involvement of students in the learning process then is limited.  It often happens only during midterm and final exams.  Students try to understand all the class material in a very short period of time closed to the exams. The effectiveness of learning process is very low. A classroom becomes a place where an instructor teaches and not where students learn.  Hence, improvement is inevitably needed in the learning process, materials, method, management of class, and also in the assessment system. This study explores an alternative learning method, namely case-based learning and cooperative learning method in student-centered learning method's context. Various researches indicate that these alternative learning methods are not only able to improve learning achievement, but they are also able to increase non-cognitive ability, such as self-esteem, communication and interpersonal relation, and learning to learn.  I apply these learning methods in Behavioral Accounting class at Faculty of Economics, Diponegoro University. At the end of the class, I distributed questionnaires to students and analyzed the answer to examine the effectiveness of learning model. The results of applying these learning methods indicate greater benefits both to the instructor and the students, compared to traditional learning method. I argue that these learning methods can optimize intellectual, social, emotional, and language potency of the students.